Rapid preparation of highly transparent piezoresistive balls for optoelectronic devices. Issue 18 (5th February 2020) - Tong, Ruiping; Cai, Ling; Chen, Guangxue; Tian, Junfei; He, Minghui
Abstract : Highly transparent piezoresistive balls are rapidly prepared for optoelectronic devices by photopolymerization of polymerizable deep eutectic solvents. Abstract : We report a rapid fabrication strategy of highly transparent piezoresistive balls with excellent pressure-sensitivity and toughness by photopolymerization of polymerizable deep eutectic solvents. By careful design and integration, a number of optoelectronic devices have been constructed with the piezoresistive balls as building blocks.